The effects of heat treatment and modified atmosphere packaging on the storage stability of noni (Morinda citrifolia L.) fruit - Z., Nuraisyah; Mohamad Azman, Ezzat; S., Radhiah; L., Prima (Rynnye Lyan Resources, 2021)
Noni fruit (Morinda citrifolia L.) is a herbal remedy known for its therapeutic and nutritional value. However, it is perishable and subject to rapid postharvest deterioration that shortens its shelf life during storage. Therefore, this study investigated whether hot water dipping (HWD; 60°C, 1 min) and Modified Atmosphere Packaging (MAP; carbon dioxide and nitrogen) could prolong noni's shelf life. The noni physicochemical properties such as colour, firmness, weight loss, total soluble solids, titratable acidity and scopoletin content were monitored during six days of storage at room temperature. During storage, the noni skin colour changed from greenish-yellow to translucent yellow, but HWD storage was stopped on day 2 due to black spots' formation. The reduction of weight loss was significantly lowest in both MAP treatments (1.39–1.74%). Among these, N2-based had a significantly higher scopoletin content (27.12 mg/g) and firmness (0.8 N) compared to CO2-based, suggesting that it was the most effective postharvest treatment to efficiently prolong the shelf life and retained the quality and stability of noni during storage.